A video encryption in HEVC entropy coding based on magic square - Bowen XU; Xiaodong WANG; Lei GUO; Jian WANG (Dianxin kexue)
In view of the multimedia information security,based on the entropy module on high efficiency video coding (HEVC/H.265),combined with the magic square,a real time and high efficiency encryption technique for high-definition video streaming was proposed.The algorithm which had an effective use of transform coefficient sparsity enabled coefficient group (CG) of transform block (TB) scrambling,and used a selective encryption on syntax elements in CG's entropy.The experiments prove that the investigated scheme has high security,which can guarantee the standard compliance and the demand of video encryption while having a low impact on encoding-rate performance.